Pengembangan Aplikasi Pembelajaran Gerbang dan Rangkaian Logika Memanfaatkan Augmented Reality Untuk Siswa SMK - Alamin, Mochammad Machlul; Pramana, Anggay Luri (Universitas PGRI Semarang, 2023)
As time goes by, technological developments are getting faster, one of which is mobile technology. In mobile technology in this era, what is often used is the use of augmented reality technology. The following study aims to provide an overview of several steps involved in making augmented reality-based Android learning media applications, gate materials, and a series of computer system lesson logic for vocational level students. In addition, to produce android learning media applications utilizing augmented reality logic circuit material for vocational level students that are practical, effective and valid. In this research, the type is application development. The process of developing this application applies the ADDIE method which is composed of five stages, namely Analysis, Design, Development, Implementation and Evaluation. From this study, the average score of validity of android mobile learning applications using augmented reality gates and logic circuits for vocational students is 4.54 and is included in the very valid section. The response results showed that students responded positively to mobile learning media, augmented reality-based logic circuits. From student responses, 80% of students responded in agreement to each part of the response, and 85% of students obtained scores above the minimum completeness criteria so that the use of logic circuit learning applications using augmented reality is categorized as effective.Â Â